Assessment of Foveal Avascular Zone and Macular Vascular Plexus Density in Children With Unilateral Amblyopia: A Systemic Review and Meta-Analysis - Gao, Lei; Gao, Yang; Hong, Fengrong; Zhang, Peng; Shu, Xiangwen (Frontiers in Pediatrics, 2021)
Purpose: To examine the quantitative measurements of OCTA in children with amblyopia using the meta-analysis methodology. Methods: PubMed, Embase, and Cochrane library were searched for available papers up to March 2021. Weighted mean differences (WMD) were used to compare the retina parameters between the eyes with amblyopia and the contralateral eyes or healthy control eyes. Results: Twelve studies were included. When considering the parafovea, the microvessel density was reduced in amblyopic eyes compared with healthy control eyes in the superficial capillary plexus (SCP) in 6×6 volume scan (WMD=-2.12, 95%CI: -3.24, -0.99) but not SCP in 3×3 volume scan (WMD=-1.43, 95%CI: -2.96, 0.11). In the deep capillary plexus (DCP), amblyopia did not decrease vessel density in the 6×6 volume scan (WMD=-2.22, 95%CI: -5.86, 1.42; I2=79.6%, P=0.008), but a difference was observed in the whole eye 3×3 (WMD=-1.95, 95%CI: -3.23, -0.67; I2=27.5%, P=0.252). There were no significant differences in the foveal avascular zone area and foveal thickness between amblyopic eyes and healthy control eyes. There were no significant differences in microvessel density, foveal avascular zone area, and foveal thickness between amblyopic eyes and fellow eyes. Conclusion: According to OCTA, amblyopic eyes had lower vessel density in parafoveal SCP and DCP compared with healthy control eyes, but not compared with fellow eyes. There were no significant differences regarding the foveal avascular zone area and foveal thickness between amblyopic and non-amblyopic eyes.